2016
DOI: 10.1186/s40824-016-0080-4
|View full text |Cite
|
Sign up to set email alerts
|

MG-63 osteoblast-like cell proliferation on auxetic PLGA scaffold with mechanical stimulation for bone tissue regeneration

Abstract: BackgroundAuxetic scaffolds (experimental) was fabricated by using poly(D, L-lactic-co-glycolic acid), 50:50, (PLGA) for effective bone cell proliferation with mechanical stimulation.MethodsNegative Poisson’s ratio in scaffold, 3-directional volumetric compression was applied during the scaffold fabrication at adequate temperature (60 °C). The pore size of scaffold ranged between 355 and 400 μm.ResultsThe porous morphology of the prepared auxetic scaffolds had shown partially concave and dent shapes in SEM ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…When PLGA is prepared in the form of volumetric structure or mixed with other materials, it usually needs 8 weeks or more to be degraded. 20,21 In other previous studies, 50%-80% of the encapsulated drug was released within less than 12 hours upon bursting of the PLGA particles. 22,23 In this study, the amount of released EGCG was calculated and expressed as a percentage of the amount added during the initial particle preparation.…”
Section: Discussionmentioning
confidence: 88%
“…When PLGA is prepared in the form of volumetric structure or mixed with other materials, it usually needs 8 weeks or more to be degraded. 20,21 In other previous studies, 50%-80% of the encapsulated drug was released within less than 12 hours upon bursting of the PLGA particles. 22,23 In this study, the amount of released EGCG was calculated and expressed as a percentage of the amount added during the initial particle preparation.…”
Section: Discussionmentioning
confidence: 88%
“…Cell proliferation was measured using the Cell Counting Kit-8 (CCK-8, Dojindo, Co. Ltd.) at 1, 3, 5, and 7 days after cell seeding. The CCK-8 solution (20 μL) was added to each well of the 24-well plates containing the cell-seeded fibrous matrices and maintained in an incubator for 1.5 h [ 26 ]. The sample extracts were transferred to 96-well plates and their absorbances at 450 nm were measured by using a microplate reader (Spectramax Plus 384, Molecular Devices, Co. Ltd., Philadelphia, USA) [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The convex porous PLGA scaffold was successfully transformed into a reentrant porous form that had special pore structures and NPR. Our previous study revealed that this structure could deliver a compressive load isotropically to cells in the scaffold, and it had an effect on cell proliferation [33,34]. In this study we investigated which type of compressive stimulation, that is, static or dynamic, could be more effective in bone cell proliferation.…”
Section: Resultsmentioning
confidence: 99%